Pengaruh Green Packaging Terhadap Purchase Intention Konsumen MCdonald’s Semarang Melalui Mediasi Product Satisfaction dan Brand Trust - Handoko, Devina Nathania; Yustini W, Retno; Atanasius, Sentot Suciarto (JEMAP, 2024)
Food entrepreneurs currently still use plastic bags as their packaging, where 65.5% of food and beverage entrepreneurs use plastic bags. McDonald's as one of the food entrepreneurs in Indonesia currently adopts the use of paper as its food packaging. The purpose of this study was to determine the effect of green packaging on the purchase intention of McDonald's consumers in Semarang and product satisfaction and brand trust as mediators of the influence of green packaging on the purchase intention of McDonald's consumers in Semarang. The population in this study were McDonald's Semarang consumers on Jalan Pandanaran Semarang. The number of samples in this study was 100 respondents of McDonald's consumers on Jalan Pandanaran Semarang. The data collection technique used in this study was using a questionnaire. The data analysis method was the Structural Equation Model (SEM). The results showed that green packaging did not have a significant effect on the purchase intention of McDonald's consumers in Semarang. Product satisfaction and brand trust became mediators of the influence of green packaging on the purchase intention of McDonald's consumers in Semarang. The operational contribution of the results of this study is that these results can be a consideration for McDonald's to improve its packaging to be more eco-friendly so that it can increase purchasing interest. The novelty of this research is the use of green packaging as an independent variable to determine purchasing interest